UMKM DEVELOPMENT IN RURAL AREAS: INTEGRATION OF EDUCATION AND COMMUNITY SERVICE - Aslan Aslan; Moh. Imron Rosidi (Adiba Aisha Amira, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) in rural areas is one of the key strategies in improving the economy and welfare of rural communities. This study aims to examine the effectiveness of the integration of education and community service in the development of MSMEs in rural areas. The method used is a literature study. The results show that the integrated approach of education and community service has a significant positive impact on the growth and sustainability of rural MSMEs. Education that covers aspects of business management, finance, marketing, and technology, combined with community service in the form of direct assistance, is proven to increase the capacity and competitiveness of MSME actors. In addition, this approach also encourages community empowerment and village economic independence. This research concludes that the integration of education and community service is an effective strategy in the development of MSMEs in rural areas